The Caucasus as a major hotspot of biodiversity: Evidence from the millipede family Anthroleucosomatidae (Diplopoda, Chordeumatida) - Antić, Dragan Ž.; Makarov, Slobodan E. (Zootaxa, 2016)
Fifteen new genera and 36 new species of the diplopod family Anthroleucosomatidae Verhoeff, 1899 are described from the Caucasus, one of the world’s biodiversity hotspots: Golovatchosoma bacillichaetum gen. et sp. nov., G. trichochaetum sp. nov., Alpinella waltheri gen. et sp. nov., Brachychaetosoma turbanovi gen. et sp. nov., Caucaseuma elephantum sp. nov., C. fanagoriyskaya sp. nov., C. glabroscutum sp. nov., C. kelasuri sp. nov., C. minellii sp. nov., C. variabile sp. nov., Caucasominorus billi gen. et sp. nov., C. polylobatus sp. nov., Georgiosoma bicornutum gen. et sp. nov., Heterocaucaseuma feminaepectorum gen. et sp. nov., H. longicorne sp. nov., Paranotosoma attemsi gen. et sp. nov., P. cordatum sp. nov., P. subrotundatum sp. nov., Dentatosoma denticulatum gen. et sp. nov., D. magnum sp. nov., D. zeraboseli sp. nov., Enghoffiella insolita gen. et sp. nov., Metamastigophorophyllon hamatum sp. nov., M. lamellohirsutum sp. nov., M. torsivum sp. nov., Acanthophorella barjadzei gen. et sp. nov., A. chegemi sp. nov., A. irystoni sp. nov., Cryptacanthophorella manubriata gen. et sp. nov., Flagellophorella hoffmani gen. et sp. nov., Pseudoflagellophorella eskovi gen. et sp. nov., P. mirabilis sp. nov., P. papilioformis sp. nov., Herculina oligosagittae gen. et sp. nov., H. polysagittae sp. nov., Vegrandosoma tabacarui gen. et sp. nov. All anthroleucosomatids from the Caucasus, both new and previously described, are classified in eight endemic complexes, arranged as follows in alphabetic order: the Alloiopus complex, the Caucaseuma complex, the Dentatosoma complex, the Enghoffiella complex, the Flagellophorella complex, the Herculina complex, the Ratcheuma complex and the Vegrandosoma complex. The genus Metamastigophorophyllon Ceuca, 1976 (the type-species: Mastigophorophyllon giljarovi Lang, 1959, adequately redescribed from new material), is a new subjective senior synonym of Persedicus Mauriès, 1982, syn. nov., being also newly transferred from the family Mastigophorophyllidae to the family Anthroleucosomatidae, comb. nov. The following two new combinations are also proposed: Heterocaucaseuma mauriesi (Golovatch and Makarov, 2011), comb. nov. ex Anamastigona Silvestri, 1898; and Metamastigophorophyllon martensi (Mauriès, 1982), comb. nov. ex Persedicus Mauriès, 1982. An identification key to and distribution maps for all known species of Caucasian Anthroleucosomatidae are provided, as well as brief remarks on distributions and on cave-dwelling taxa.